2020
DOI: 10.1111/cid.12886
|View full text |Cite|
|
Sign up to set email alerts
|

Data on implant failures will show different results depending on how patients are compiled and analyzed: A retrospective study on 3902 individual patients treated either with one single implant or implants in the edentulous upper jaw

Abstract: Purpose The basic aim of the present study was to analyze the results of implant failures in two different implant populations, and how these results may vary depending on how the data are compiled and analyzed. Materials and Methods Two groups of consecutively treated patients were included who had been provided with either one single implant in a partially edentulous upper jaw (1881 patients) or four to eight implants in an edentulous upper jaw (2031 patients/12 454 implants). The risk of implant failure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…3,21 The subsequent free-hand implant hole shaping can simply enlarge the pilot hole, but adjustments can also be made based on the surgeon's experience to avoid lateral alveolar perforation or breakage. 22 Several limitations of this study should be acknowledged. First, this was a retrospective study with inherent limitations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…3,21 The subsequent free-hand implant hole shaping can simply enlarge the pilot hole, but adjustments can also be made based on the surgeon's experience to avoid lateral alveolar perforation or breakage. 22 Several limitations of this study should be acknowledged. First, this was a retrospective study with inherent limitations.…”
Section: Discussionmentioning
confidence: 92%
“… 3 , 21 The subsequent free-hand implant hole shaping can simply enlarge the pilot hole, but adjustments can also be made based on the surgeon’s experience to avoid lateral alveolar perforation or breakage. 22 …”
Section: Discussionmentioning
confidence: 99%
“…The causal explanation of implant failure is more complex and is what many studies are trying to report. It is speculated that failure of an implant may occur as a result of a combination of multiple factors and the evaluation of this association may cause variations in the results depending on the chosen statistical method 32 . In a recent study, the authors demonstrated better results were obtained using the Bayesian statistical method relative to classical statistical analysis 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The 31 publications on clinical studies, regarded 20 RCTs (Table 2) (Akoglu et al, 2011;Burtscher et al, 2015;Cehreli et al, 2010;Donati et al, 2018;Gotfredsen, & Karlsson, 2001;Ioannidis et al, 2019;Jacobs et al, 2010;Koller et al, 2020;Lee et al, 2016;Ma et al, 2010;Mau et al, 2002Mau et al, , 2003Meijer et al, 2009;Menini et al, 2015;Nickenig et al, 2013;Raes et al, 2018;Ravald et al, 2013;Roccuzzo et al, 2008;Vroom et al, 2009;Wennström et al, 2004;Zetterqvist et al, 2010), 3 prospective non-randomized CTs (Table 3) (Bornstein et al, 2008;De Angelis et al, 2020;Guarnieri et al, 2018), 4 PCs (Table 4) (Baelum, & Ellegaard, 2004;Friberg, & Jemt, 2015;Meijer et al, 2014;Tymstra et al, 2012) and 4 RSs (Table 5) (Jemt, 2020;Maló et al, 2016;Wada et al, 2019;Wagenberg et al, 2013).…”
Section: Overview-implant Characteristics-reported Outcomesmentioning
confidence: 99%
“…The 4 publications reporting on RSs included 541-3912 patients each (5630 patients in total), who had received 21,133 implants; follow-up time ranged from 1 to 30 years, with 3 publications reporting on an average follow-up time of about 8 years or more (Jemt, 2020;Maló et al, 2016;Wagenberg et al, 2013) (Table 5). In 3 publications (Jemt, 2020;Maló et al, 2016;Wagenberg et al, 2013), implants with turned and with modified surface were included, while the last publication (Wada et al, 2019) reported on implants with various type of modified surfaces. The majority of patients were fully edentulous, and implants supported both fixed and removable den-…”
Section: Rssmentioning
confidence: 99%